Penerapan Reading Guide Dalam Pembelajaran Di Madrasah - Sutomo, Moh. (AULADUNA, 2019)
Learning about religious education still uses many conventional methods, where this method requires students to agree with what the teacher has said. The teacher does not familiarize students to be more active than teachers, even though in the present era the demands of the times really need output that is reliable in all things. Problems that are often encountered in lessons, especially Islamic teaching is how to present material to students well and efficiently. Keywords: Application, Reading Guide, Learning